Residential Building Envelope Alternatives with Equivalent Cost - BOSTANCIOĞLU, ESRA (Gazi Üniversitesi, 2011)
Selecting the optimum envelope alternative in buildings is one of the most important factors in ensuring thermal comfort. This study calculated the heating costs, construction and lifecycle costs for a residential building in Istanbul with different envelope alternatives created by changing the type and thickness of the body and insulation materials used in the walls and roof, which are the structural components forming the building envelope. Envelope alternatives with equivalent costs were determined and evaluated. Hence, materials with varying properties and thicknesses were able to yield the same performance in terms of lifecycle and heating costs.
Keywords: energy efficiency; envelope design; envelope alternatives with equivalent cost; life cycle cost; heating cost